2010
DOI: 10.1364/ol.35.002588
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabroadband optical circular polarizers consisting of double-helical nanowire structures

Abstract: Recently, it was demonstrated by Gansel et al. [Science 325, 1513 (2009)] that 3D single-helical metamaterials can serve as broadband circular polarizers in the IR range. In this study, we propose a structured metamaterial with double-helical nanowires to construct circular polarizers with boarder wavelength bands in the visible-light and near-IR regions. Using the finite-difference time-domain method, we confirmed that the circular polarizers with the double-helical structures have operation bands more than 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 15 publications
0
72
0
Order By: Relevance
“…N-helices have been proposed several years ago [10][11][12], but certain constraints due to their principle of operation have only been studied later for the case of N = 4, 8, 12, ... [14]. We have shown that the four-fold rotational symmetry strictly eliminates off-diagonal elements in the Jones transmission and reflection matrices in circular polarization basis, provided that no diffracted orders other than the two 0-th orders occur.…”
Section: Symmetry and Reciprocitymentioning
confidence: 95%
See 1 more Smart Citation
“…N-helices have been proposed several years ago [10][11][12], but certain constraints due to their principle of operation have only been studied later for the case of N = 4, 8, 12, ... [14]. We have shown that the four-fold rotational symmetry strictly eliminates off-diagonal elements in the Jones transmission and reflection matrices in circular polarization basis, provided that no diffracted orders other than the two 0-th orders occur.…”
Section: Symmetry and Reciprocitymentioning
confidence: 95%
“…Linear birefringence is equivalent to circular polarization conversions. By intertwining several helices in one unit cell, these conversions can be eliminated [10][11][12]. N = 2 helices (untapered and tapered [13]) exhibit even more obviously an unwanted linear birefringence.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce or eliminate these unwanted polarization conversion effects, multiple (integer N) intertwined helices have previously been proposed [10,11]. For N = 2, they can be seen as the analog to the DNA double strands in biology.…”
Section: Introductionmentioning
confidence: 99%
“…Rotational symmetry, intrinsically lacking in helix geometry, can be effectively restored with a packed multihelix arrangement in a single cell by the multihelical nanowire (MHN) configuration (similar to DNA strands), which have been recently theoretically proposed 20,[25][26][27][28] . MHNs are predicted to operate as broadband circular polarizers in the visible range with high purity of circularly polarized transmitted light.…”
mentioning
confidence: 99%